A "Sense of Presence": The "me of me" in Black Girlhoods. Issue 1 (1st March 2022) - Mitchell, Claudia; Smith, Ann
Abstract : We begin by paying tribute to feminist Black scholar, bell hooks, who died 15 December 2021. As the numerous citations in just this issue alone bear witness, she has had a huge influence on feminist ways of thinking particularly in relation to how race, gender, and capitalism intersect. In her well-known essay, "In Our Glory" on Black girlhood and visual culture (hooks 1994 ), she offers a memory of losing a photograph of herself as a young girl in the 1950s masquerading, as she called it, in full cowgirl regalia.